Exploring the cognitive effects of bilingualism: neuroimaging investigations of lexical processing, executive control, and the bilingual advantage - Coderre, Emily L. (2012)
Bilingualism has been shown to influence a variety of cognitive functions, most notably lexical processing and cognitive control. These effects are both detrimental and advantageous. On the one hand, it has been proposed that bilinguals experience delayed lexical access compared to monolinguals, both in the less-proficient language and in the native language, due to the relatively reduced frequency of use. On the other hand, the constant need to juggle and control two languages enhances cognitive control abilities in bilinguals, such that they outperform monolinguals on tasks of executive processing and conflict resolution. This dissertation explores these cognitive changes associated with bilingualism, primarily through the use of a Stroop task. As it combines lexical processing with cognitive control, the Stroop task is a unique paradigm in which to investigate these abilities in bilinguals. Using behavioural measures, electroencephalography, and functional magnetic resonance imaging, the experiments presented here seek to deepen our understanding of lexical processing and cognitive control in bilingualism, in order to better understand how the now-common use of multiple languages affects the functional brain.